Is participation contagious? Evidence from a household vector control campaign in urban Peru. Issue 2 (23rd September 2013) - Buttenheim, Alison M; Paz-Soldan, Valerie; Barbu, Corentin; Skovira, Christine; Quintanilla Calderón, Javier; Mollesaca Riveros, Lina Margot; Cornejo, Juan Oswaldo; Small, Dylan S; Bicchieri, Christina; Naquira, Cesar; Levy, Michael Z
Abstract : Objectives: High rates of household participation are critical to the success of door-to-door vector control campaigns. We used the Health Belief Model to assess determinants of participation, including neighbour participation as a cue to action, in a Chagas disease vector control campaign in Peru. Methods: We evaluated clustering of participation among neighbours; estimated participation as a function of household infestation status, neighbourhood type and number of participating neighbours; and described the reported reasons for refusal to participate in a district of 2911 households. Results: We observed significant clustering of participation along city blocks (p<0.0001). Participation was significantly higher for households in new versus established neighbourhoods, for infested households, and for households with more participating neighbours. The effect of neighbour participation was greater in new neighbourhoods. Conclusions: Results support a 'contagion' model of participation, highlighting the possibility that one or two participating households can tip a block towards full participation. Future campaigns can leverage these findings by making participation more visible, by addressing stigma associated with spraying, and by employing group incentives to spray.